Nick Hornby’s A Long Way Down (2005) in the Transition from Book to Movie - Tüm, Ömercan (Journal of History Culture and Art Research, 2015)
Nick Hornby’s A Long Way Down (2005) in the Transition from Book to movie Abstract Challenging and profound, Nick Hornby’s novel A Long Way Down (2005) is the story of four people failing to commit suicide. The protagonists are caught in an intricate web of relationships, disappointments and missed chances on their one-way journey to understand that “The cure for unhappiness is happiness” (Elizabeth McCracken). This paper aims at demonstrating that 2014 movie version directed by Pascal Chaumeil fails to capture the essence of the book and resorts to a number of radical changes which are only supposed to attract a larger audience, but do not necessarily send the same message as the novel.